Pengaruh Pembiayaan Murabahah dan Musyakarah Terhadap Permintaan Nasabah Dalam Memilih Produk KPR di Bank BTN KCPS Meulaboh - Junita, junita; Alisman, Alisman (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2024)
In everyday life, housing and settlement problems are one of the obstacles that always attract more attention from the government. The human need for shelter is a basic need without distinction of ethnicity, race or religion. For people from the lower middle class, buying a house in cash is one of the many obstacles currently occurring. So many people prefer to buy a house on credit. Due to the large number of requests from the public, this opportunity is being exploited by many financial and banking institutions, as well as Sharia Banks. Sharia Bank is a bank whose operational system does not use an interest system, but uses basic principles in accordance with Islamic sharia. One of the financing facilities provided by sharia banks is Home Ownership financing. The murabahah bil wakallah contract is a sale and purchase agreement using the wakalah system, the purpose of this sale and purchase is that the bank represents the purchase to the customer, so the first contract that occurs is the wakallah contract. Meanwhile, the musyaraqah mutanaqisah contract is a derivative product of the musyaraqah mutanaqisah contract, namely a form of cooperation contract between two or more parties. The purpose of this research is to determine the financing of murabahah bil wakalah contracts and musyarakah mutanaqisah contracts against customer demand at Bank BTN KCPS Meulaboh. This research was carried out by going directly into the field to gather information about the level of demand for iB KPR financing products with Murabahah contracts through direct interviews with related parties, namely Bank BTN KCPS Meulaboh. Data analysis techniques use descriptive analysis, classical assumption test, coefficient of determination test, t test and multiple linear regression. The research results show that the R square value for murabahah financing is 0.020 or 2 percent. The R square value means that demand can be influenced by murabahah financing by 2 percent and the rest is influenced by other variables not included in this research. Meanwhile, the R square value for deliberative financing is 0.039 or 3.9 percent. The R square value means that demand can be influenced by deliberative financing by 3.9 percent and the rest is influenced by other variables not included in this research